Multiscale Surface Roughening of Commercial Purity Titanium during Uniaxial Tension; AIP Conference Proceedings; Vol. 1683 : Advanced Materials with Hierarchical Structure for New Technologies and Reliable Structures - Panin A. V. Alexey Viktorovich; Kazachenok M. Marina; Kozelskaya A. I. Anna Ivanovna; Sinyakova E. Elena; Lider A. M. Andrey Markovich; Sklyarova E. A. Elena Aleksandrovna (2015, 2015)
Title screen